SANITATION CONDITIONS OF TRADITIONAL MARKET ON SEDANAU ISLAND, NATUNA REGENCY, INDONESIA 2023 - Pitriyanti, Luh; Kartika, Yuni (Bajang Institute, 2024)
A healthy market is a place where all related parties work together to provide safe, nutritious and healthy food from an environment that meets health requirements. Poor access to sanitation in markets can result in various diseases. The specific aim of this research was to provide an overview of market locations, market buildings, market sanitation, market sanitation management, community empowerment and clean and healthy living behavior in the market, market safety, and an overview of market supporting facilities. The method in this research was observation using an observation sheet. The location in this research was carried out at the West Bunguran Sedanau Island Traditional Market which was carried out in July 2023. The results of this research showed that the market location met the requirements (80%), the market building did not meet the requirements (42%), market sanitation did not meet the requirements (53 %), market management does not meet the requirements (0%), community empowerment and clean and healthy living behavior does not meet the requirements (14%), market security does not meet the requirements (0%), supporting facilities do not meet the requirements (0%).